Evaluating coronary artery disease in type 2 diabetes mellitus and Other Risk Factors by angiographic study - AL-rubae, Salim M. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Diabetes mellitus (DM) is a metabolic and vascular illness associated with two to four times coronary artery disease (CAD) events and mortality which correlate well with fasting, postprandial plasma glucose and HbA1c level. Other factors such as aging, gender, smoking, dyslipidaemia and hypertension also play an important role in diabetic micro- and macro-vascular complications. Type 2 DM is reported now to be CAD equivalent.Patients and Methods: A cross sectional study of 118 patients including 90 males and 28 females being 63 diabetics and 55 non-diabetics over the period from March-November 2007 in Iraqi center for cardiac diseases who were underwent coronary angiographic study.Results: By angiographic study CAD was present in 92.1% of diabetic versus 89.1% in non diabetic patients. Single, double and triple vessels diseases were found in 15.9%, 22.2%, and42.9% of diabetics versus 16.4%, 21.8%, 34.5% in non diabetics respectively. DM and dyslipidaemias were proved to be independent risk factors for left circumflex artery (LCX) disease predilection (p value